A SURVEY REGARDING THE QUALITY OF FINANCIAL STATEMENTS - MILOȘ, Marius Cristian; MILOȘ, Laura Raisa (Annales Universitatis Apulensis Series Oeconomica, 2014)
The paper aims at bringing arguments for the necessity of improvement of the financial statements of the companies. After highlighting the limitations of the information included in the financial statements and proposing some measures of qualitative improvement, there are analyzed the results of a survey, performed in the western area of Romania, that wanted to seize the needs and expectations of the users as far as concerns the accounting and financial information provided by the Romanian companies.